图书馆如何支持大学创新？--以新加坡南洋理工大学图书馆为例 = Supporting University innovation : a case study of NTU Library - 阮阳 Ruan, Yang (2010)
为适应知识经济时代需要，培育全方位创新人才，近年来新加坡南洋理工大学（以下简称南大）在教学科研方面推进了一系列改革和创新。南大图书馆作为大学教学、科研的辅助部门，担负着配合学校教学和科研的重要职责，必然要开展各种创新服务以积极配合并大力支持大学创新；同时，图书馆创新也是图书馆自身适应时代发展和满足读者需求的必然反应。本文重点介绍了近年来我馆在创新方面的一些实践经验，如增设学习共享空间（learning commons），提供Web 2.0新技术服务，实施“口袋图书馆”( library-in-your-pocket ) 的理念，开展移动信息服务，建立学科室（subject room）、深化学科信息服务，建立南大机构典藏(DR-NTU)等。 特此与同行分享。下文将分为四大部分，第一部分简要介绍大学概况，第二部分介绍近年来大学的主要发展创新，第三部分重点介绍图书馆在支持大学创新方面的各项创新举措，第四部分是总结和未来展望。In recent years, Nanyang Technological University (NTU) has embarked on a strategic thrust to develop into a research intensive university. At the same time, NTU is also undertaking a major revamp of the undergraduate education to ensure that our graduates “develop the ability of lifelong learning to meet the challenges of rapidly changing demands, nurture a sense of adventure, entrepreneurship and leadership, and imbibe the latest technological developments that would serve them well when they first enter the workplace”.